(untitled) - SANTOSO, EKO (Jurnal Ilmu Manajemen (JIM), 2013)
Initial return is the shareholder benefits from the differencebetween the initial public offering with the stock closing price on thesecondary market on the first day. Initial public offering (IPO) of thecompany is one of the ways companies get funds from the public.IPO is the first step to determine the viability of a public company.The purpose of this study was to analyze the effect of financialperformance, firm size, underwriter reputation, and auditor reputationon initial return. Sampling was conducted using purposive samplingmethod which produces 83 companies as the study sample. Multiplelinear regression was used to examine the relationship between thedependent and independent variables. Results showed that the effectof independent variables simultaneously on the initial return. Partially,auditor reputation is significant negative effect on initial return,whereas financial performance, firm size and underwriter reputationdoes not affect the initial return.Keywords: initial return, financial performance, firm size, underwriter reputation, and auditor reputation.